Aid with Multiple Personalities - Djankov, Simeon; Montalvo, Jose G.; Reynal-Querol, Marta (2012)
The existing research on foreign aid offers inconclusive evidence on the factors that make aid effective. In this paper, we study the supply of aid money in 112 developing countries over the period 1960-1999 and find that the presence of multiple donors in a given country renders aid less effective. In particular, an aid-receiving country at the median of the donor fractionalization distribution will grow one percentage point faster than a country at the 75th percentile. This is in part because donor fragmentation is associated with increased corruption in the recipient country's government.